Theoretical Analyses, Computations, and Experiments of Multiscale Materials A Tribute to Francesco dell$1 (BIsola /s - Giorgio, Ivan.; Placidi, Luca.; Barchiesi, Emilio; Abali, Bilen Emek.; Altenbach, Holm.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is devoted to the 60th birthday of the Prof. Francesco dell$1 (BIsola, who is known for his long-term contribution in the field of multiscale materials. It contains several contributions from researchers in the field, covering theoretical analyses, computational aspects and experiments. .s
1. A Different Catch for Poisson -- 2. Nonlinear Deformation of a Clamped-Edge Strip-Like Nano-Film -- 3. Closed-form Analytic Solutions of the Problem of a Hollow Sphere Made of Second Gradient Plastic Porous Material and Subjected to Hydrostatic Loading -- 4. Quantum Dynamics Effects on Amplitude-Frequency Response of Superharmonic Resonance of Second-Order of Electrostatically Actuated NEMS Circular Plates -- 5. Propagation of Chaos for a Stochastic Particle System Modelling Epidemics.
Keywords: Mechanics, Applied; Solids; Mechanics; Continuum mechanics; Solid Mechanics; Classical Mechanics; Continuum Mechanics; Nanostructured materials